Vigilant Care: Experiences of In-Home Caregivers of Coronavirus Disease 2019 Patients - Nasrin Dadashi; Marzieh Pazokian; Mahmood Motamedzadeh (Mashhad University of Medical Sciences, 2022)
Background: Home care is always appreciated as an effective alternative method to manage critical conditions, expand hospital capacity, and admit further cases suspected of more severe clinical symptoms.Aim: The present study aimed to reflect on the experiences of in-home caregivers of patients with coronavirus disease 2019 (COVID-19) in Iran.Method: For this qualitative descriptive study, 13 participants (i.e., the Iranian family caregivers of patients with COVID-19) were selected and included using the purposive sampling method. Caregivers were those who accompanied the patient to the outpatient department for three months from 22 June to 22 August 2021. An interview was conducted in a private room with family caregivers of patients. The data were obtained through a series of semi-structured interviews, each one lasting 30-40 min. The data were completed via the MAXQDA software (version 10). Analysis was performed according to the approach of Granheim and Landman 2004 by the conventional content analysis method.Results: The results lead to the emergence of the final theme "vigilant care" containing four categories (e.g., Quarantine fence, Economic management as a bottleneck, Confusion and difficulty in care, as well as Conflicting adaptation and mitigation of psychological stress) and 14 subcategories.Implications for Practice: Vigilance care is a major challenge for caregivers of patients with Covid-19 at home. Therefore, providing educational solutions or training booklets in outpatient wards during discharge can partially resolve the ambiguities and be effective in improving care.